Specialized nursing terminology for the care of people affected by stroke (Revista Científica Integrada, 2024)
Objective: To develop specialized nursing terminology for the care of people affected by stroke in the context of primary health care, based on the International Classification for Nursing Practice (ICNP®). Method: The methodological study developed in three stages: 1) Identification of terms and/or concepts of professional nursing language about people affected by stroke in the context of primary care; Stage 2 - Cross-mapping of the identified terms with terms from the International Classification for Nursing Practice version 2019/2020; and, Stage 3 - Classification of the identified terms according to the Seven-Axis Model of ICNP® version 2019/2020. Results: A total of 4,588 terms were identified, and after manual selection, 113 terms were obtained, which were mapped with the ICNP® and analyzed for degree of equivalence, obtaining: 101 (89.38%) constant terms, of which 89 (78.76%) had degree of equivalence 1 and 12 (10.61%) had degree of equivalence 2; 12 (10.61%) non-constant terms, of which 4 (3.54%) had degree of equivalence 4 and 8 (7.07%) had degree of equivalence 5; no terms were found that covered degree of equivalence 3. Conclusion: A specialized nursing terminology was constructed for the care of people affected by Stroke, in the context of Primary Health Care.
Keywords: Stroke; Primary Health Care; Standardized Nursing Terminology